Atherosclerosis in rat PCOS model induced by testosterone propionate combined with high fat high fructose diet - Sularto, Dirwan Suryo; Wahyuni, Alfaina (Institute of Computer Science (IOCS), 2023)
Atherosclerosis is closely related to the metabolic syndrome like what occurs to Polycystic Ovary Syndrome (PCOS). The recent increase in prevalence due to high calories diet and high carbohydrate, infrequent exercise, and the escalating obesity trend increased insulin resistance. PCOS is linked to many long term health problems, such as cardiovascular disease, atherosclerosis, and diabetes. How is the potential of atherosclerosis for PCOS model mice induced with testosterone propionate and high fat diet and high fructose? This research is important to conduct in order to determine the potential of atherosclerosis for PCOS through the observation on mice model of PCOS. This research employed Postest Only Control Group Design method. Twenty female Rattus norvegicus strain Wistar mice weighing between 100 and 130 grams, aged 3 months, served as the samples. After observing estrous cycle, 15 mice were randomly chosen to be made PCOS model induced with testosterone propionate 1mg/100 g BW/day intramuscularly combined with high fat diet and high fructose. The treatment was given on day 18, 21, and 24. Afterwards, the mice were sacrificed on day 19, 22, and 25. After 12 hours of fasting the mice, the mice were sacrificed and the coronary arteries attached to the heart were taken to be made histological preparations. Then, the degree of atherosclerosis potential was observed. Statistical analysis used One Way Anova test with significance level of α=0,05. Data analysis was performed using Statistical Product and Servive Solutions (SPSS) program version 24.0 for Windows.